Analisa Histogram dan PSNR Pada Citra True Color Dalam Pengamanan Teks Menggunakan Spread Spectrum dan LSB - Rika Humayrah; Andi Marwan Elhanafi; M. Taufik Batubara (LKP Unity Academy, 2023)
Security of confidential text messages is very important to protect the contents of messages from irresponsible parties. For this reason, the importance of awareness in terms of data security in the current digital era is marked by the development of data security applications. In this study, histogram and PSNR analysis will be carried out in data security applications. The purpose of this analysis is to determine the changes in the histogram and PSNR values of the image that has been inserted a text message. The results of the message insertion in the true color image using the spread spectrum method and the least significant bit visually do not show any change. The number of inserted characters affects the histogram graph, the more the number of characters inserted, the more visible the graph changes in the histogram. The resulting stego image meets the fidelity and recovery criteria. It is evident from the resulting PSNR value, namely PSNR > 30db. Changes in the image extension are one of the factors that cause the PSNR value. It is proven by the .jpg image extension which has the lowest MSE of 0.00251 and the highest PSNR of 74,12625db.